Meningitis caused by Aspergillus fumigatus: a case report - Yifei Zhang; Yu Ma; Rushuang Yue; Yuan Meng; Yue Jin; Chengwei Yin; Qianmei Zhou; Rong Shi (BMC Infectious Diseases)
Abstract Background Aspergillus fumigatus is a common pathogen that causes intracranial aspergillosis. A. fumigatus intracranial infection mainly occurs in the brain parenchyma. Head CT or MRI examination showed aspergillous abscess, which is extremely rare to caused meningitis alone. We report a case of aspergillosis meningitis with short-term death. Method We utilized the DNBSEQ™ sequencing platform, which employs DNA nanoballs (DNBs) technology. Briefly, DNBs are arrayed on a patterned flow cell, where DNA polymerase catalyzes the incorporation of fluorescently labeled nucleotides during sequencing-by-synthesis. The emitted fluorescence signals are digitally captured and computationally processed to generate high-accuracy base sequence data. Case presentation A 51-year-old woman with a medical history of post-hepatitis B cirrhosis, type 2 diabetes mellitus, and thyroid carcinoma presented with acute-onset altered mental status. Physical examination revealed positive meningeal signs. Initial neuroimaging studies, including two serial head CT scans and two MRI examinations, showed no evidence of fungal abscess formation in the brain parenchyma. The diagnosis of A. fumigatus meningitis was confirmed through cerebrospinal fluid (CSF) analysis, including metagenomic next-generation sequencing (mNGS) and galactomannan (GM) testing. Despite prompt initiation of voriconazole therapy, the patient’s condition deteriorated, resulting in death after 10 days of treatment. Conclusion A. fumigatus meningitis represents a rare but life-threatening infection characterized by diagnostic challenges and alarmingly high mortality rates. Stringent diagnostic vigilance is essential to avoid diagnostic errors in these cases. The PMseq-DR platform, a high-throughput metagenomic sequencing technology for cerebrospinal fluid (CSF) analysis, provides a valuable diagnostic tool for rapid pathogen identification. For patients presenting with meningitis of unknown etiology following conventional diagnostic workup (including microbial culture, galactomannan assay, and 1-3-β-D-glucan testing), comprehensive CSF pathogen analysis becomes critical. In such scenarios, prompt implementation of high-throughput sequencing is recommended to enable accurate diagnosis and timely therapeutic intervention.